Measures to Mitigate Causative Factors of Budget Overrun in Malaysian Building Projects - Ullah, Kaleem; Abdullah, Abd Halid; Nagapan, Sasitharan; Sohu, Samiullah; Khan, Muhammad Shahid (International Journal of Integrated Engineering, 2019)
Completion of a construction within planned budget is one of the main criterion of project success, however budget overrun has become a recurring phenomenon in construction industry. Budget overrun can cause multiple negative effects such as loos of economy, disputes among construction stakeholders, project abandonment, and drop in construction activities. This study aims to identify causes of budget overrun in Malaysian Building projects and then to establish mitigation measures for the identified main causes. Literature review, questionnaire survey and interviews were used in this study. Detailed literature review results in identification of 28 causes of budget overrun. The main causes of budget overrun in building projects in Malaysia were investigated through a questionnaire survey of 83 contractors, 57 clients, and 40 owners. The feedback of questionnaire survey was analyzed statistically. The significant causes of budget overrun were: improper planning, variation in materials price, poor site management, lack of communication between parties, frequent design changes, incompetent contractors, mistakes during construction, shortage of site workers, delay in material procurement, and low speed of decisions making. After questionnaire survey, interviews with 16 construction exports were carried out in order to develop mitigation measures for the top ten significant causes. On the basis of interviews, a list of mitigation measures for each of the top ten significant causes were established. The findings of this study can be useful for construction practitioners in controlling budget overrun and to achieve project success.